Fios de histórias, fios de alta tensão. Eletricidade, turismo, peixes e projetos em redes envolvendo a comunidade de Pouso da Cajaíba (Paraty, RJ) - Novaes, Luana Santiago [UNIFESP] (2020)
This dissertation is the result of a fieldwork carried out between 2017 and 2019 in Pouso da Cajaíba, a coastal community in the municipality of Paraty (RJ). The work sought to launch networks on relational techniques that multiply the doings of life in Pouso: fishing, planting, institutions (such as the school and the health post), tourism, projects and politics. Starting from a conceptual image by Ingold, the dissertation tried to show how life at Pouso is constituted as a mesh of lines along which different beings and rhythms interact. Among these are the electricity lines, whose recent arrival in the Pouso community was the trigger for the research.